Urinary incontinence among elite track and field athletes according to their event specialization: a cross-sectional study - Rodríguez-López, E. S.; Acevedo-Gómez, M. B.; Romero-Franco, N.; Basas-García, Á.; Ramírez-Parenteau, C.; Calvo-Moreno, S. O.; Fernández-Domínguez, J. C. (Sports Medicine - Open, 2022)
Background: Physical effort in sports practice is an important trigger for urinary incontinence (UI). Among high-impact sports, all track and field events require continuous ground impacts and/or abdominal contractions that increase intra-abdominal pressure and impact on the pelvic floor musculature. However, studies to date have not taken into account the specific sports tasks that elite track and field athletes perform according to the competitive events for which they are training. Methods: This cross-sectional study describes the prevalence, type, and severity of UI among elite track and field athletes considering their event specialization and training characteristics. A total of 211 female and 128 male elite track and field athletes answered an online questionnaire including anthropometric measures, medical history, training characteristics, and UI symptoms. To determine self-reported UI, the International Consultation on Incontinence Questionnaire-UI Short-Form (ICIQ-UI-SF) was used. To determine UI type and severity, the incontinence questionnaire and incontinence severity index were used, respectively. Results: The ICIQ-UI-SF showed that 51.7% of female and 18.8% of male athletes had UI, with stress UI (SUI) being the most frequent type (64.4%) for female and urge UI for male athletes (52.9%). Of athletes who were not identified as having UI according to the questionnaires, 24.6% of female and 13.6% of male athletes experienced urine leakage during training, mainly during jumping. Although training characteristics (experience, volume, and resting) were not related to UI, female athletes specializing in vertical jumps showed significantly lower UI prevalence compared to those specializing in horizontal jumps (?2 [1] = 4.409, p = 0.040), middle-distance running (?2 [1] = 4.523, p = 0.033), and sprint/hurdles events (?2 [1] = 4.113, p = 0.043). These female athletes also displayed the lowest training volume. No differences were shown for males (p > 0.05). Conclusions: Over half of the elite track and field female athletes have self-reported UI, especially SUI, and prevalence is higher when considering urine leakage events during training. Training characteristics and specialization were not related to UI identified by questionnaires, but female athletes specializing in vertical jump events showed the lowest prevalence and training volume. Males showed significantly lower prevalence, without correlation with their specialization. Sport professionals should increase UI detection among elite athletes and design-specific approaches that consider their physical demands to make visible, prevent, or improve pelvic floor dysfunction in this population.